Redox Reaction Science Literacy Skills of SMAN 6 Bulukumba Students - Muzamil Falaq; Sugiarti Sugiarti; Alimin Alimin (Jambura Journal of Educational Chemistry, 2026)
One of the reasons students are not good at science literacy is the domination of conventional teacher-centered learning models. Science literacy can be enhanced only by embracing other models that are centered on the scientific process, for example, the Problem-Based Learning (PBL) model. This study examines analytically the effect of the PBL model on science literacy skills of grade XII students in SMAN 6 Bulukumba in the 2024/2025 academic year, specifically redox reactions. Applying the quasi-experimental design with the posttest control group, the study utilized a comprehensive measurement of science literacy according to the context, knowledge, and competence aspects. Test data were contrasted employing both descriptive and inferential statistical analysis. Results of homogeneity and normality testing supported that the two groups were randomly drawn from homogeneous populations, although the data were not normally distributed. Thus, hypothesis testing was carried out employing the Mann-Whitney U test, with a Zcount value greater than Ztable (1.77 > 1.64). These results indicate that the Problem-Based Learning model improves grade XII students of SMAN 6 Bulukumba adequately in terms of their chemistry literacy skills, i.e., in the field of redox reactions.